2021
DOI: 10.1016/j.ejso.2021.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal cancer index predicts severe complications after ovarian cancer surgery

Abstract: Introduction: prediction and importance of severe postoperative complications after ovarian cancer surgery is a strong issue in patient selection and evaluation. Pre-and early peroperative predictors of severe 30-days postoperative complications (Clavien-Dindo class !3) after surgery for primary ovarian cancer are not fully established, neither their impact on patients' survival. Materials and methods: A prospective observational study included 256 patients with primary ovarian cancer FIGO stages IIB-IV, opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Neither FIGO stage at diagnosis nor number of received NACT cycles appeared to affect perioperative outcomes, even if women submitted to > 4 cycles of NACT showed a trend toward a more deranged postoperative creatinine serum level and longer median hospital stay, which can be explained by (i) the higher rate of small/large bowel resection perfomed in this popualtion, (ii) by the cumulative toxicity from chemotherapy, and/or (iii) by the usual higher rate of comorbidities and disease burden among women scheduled for prolonged NACT. 6 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…Neither FIGO stage at diagnosis nor number of received NACT cycles appeared to affect perioperative outcomes, even if women submitted to > 4 cycles of NACT showed a trend toward a more deranged postoperative creatinine serum level and longer median hospital stay, which can be explained by (i) the higher rate of small/large bowel resection perfomed in this popualtion, (ii) by the cumulative toxicity from chemotherapy, and/or (iii) by the usual higher rate of comorbidities and disease burden among women scheduled for prolonged NACT. 6 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…Lomnytska et al identified the PCI as an independent predictor of high-grade complications after ovarian cancer surgery, highlighting its clinical relevance in perioperative planning and patient counseling [ 42 ]. Furthermore, Jónsdóttir et al found the PCI to be an excellent predictor of operability and survival outcomes, with higher scores correlating with increased rates of complications and reduced chances of survival [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, gynecological oncologists emphasize the risk factors associated with perioperative complications such as malnutrition, hypoalbuminemia, low transferrin levels, obesity, insulin resistance, high levels of C-reactive protein, interleukin-6 and increased platelet count (36)(37)(38). Moreover, a peritoneal cancer index ≥21 and preoperative albumin concentration ≤33 g/l were also independent predictors of high-grade complications (37,39). Although the ERAS protocol can enhance the rehabilitation of a patient, a recent study showed that 5.8% of 7,029 patients (76.5% from Caucasian ethnicity) in the national surgical quality improvement program database had experienced Clavien-Dindo IV complications, and that 0.9% of patients died within 30 days.…”
Section: Discussionmentioning
confidence: 99%